Performance criteria for structural concrete - Dinku, Abebe (Zede Journal of Ethiopian Engineers and Architects, 2023)
In this paper, the durability of concrete in general and the gaf permeability of concrete in pariicular are theoretically explained and some durability test results obtained from laboratory investigation are discussed. A simple and practical gaf permeability meafurement apparatus. which enables to assess the performance properties of concrete is presented. Test results indicated that curing duration plays a ;ignificant role in improving the performance J'roperties of concrete, and it has been shown that compressive strength alone cannot be used to assess the performance properties of concrete accurately.